Uterine Lipoleiomyoma: a rare variant of benign uterine neoplasm - Jagtap, Sunil V.; Phalke, Abhijit; Kshirsagar, Nitin S.; Jagtap, Shubham S.; Nasre, Nitesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The lipomatous tumors are very rare benign neoplasms of the uterus. Lipoleiomyoma is a benign tumor which is variant of leiomyoma. It has similar clinical course and presentation like uterine leiomyoma and is typically found in postmenopausal women. Authors report a case of 45 years female presented with a complaint of increased frequency of menstrual cycles and generalized weakness since 5- 6 months. On ultrasonography abdomen - pelvis a single large lobulated hyperechoic mass was noted in the fundal myometrium measuring 5 x 4.6 cm. The finding was suggestive of fibroid uterus. On histopathological examination showed variable proportions of lobules of mature adipocytes and interlacing bundles of benign smooth muscle cells which was diagnostic of lipoleiomyoma. Authors are presenting this case for its rarity, clinical presentation, imaging and histopathological finding with differential diagnosis.